Synthesizing ENABLE-AGE Research Findings to Suggest Evidence-Based Home and Health Interventions. Issue 3 (2nd July 2016) - Iwarsson, Susanne; Löfqvist, Charlotte; Oswald, Frank; Slaug, Björn; Schmidt, Steven; Wahl, Hans-Werner; Tomsone, Signe; Himmelsbach, Ines; Haak, Maria
ABSTRACT: As the quest for knowledge translation from research to practice and policy contexts is growing stronger, researchers need to develop strategies for synthesizing research findings. Since home environments constitute an important context for the delivery of health care and social services to older adults and people aging with disabilities, research in this field can serve as an example for such endeavors. Using 35 original publications and one unpublished doctoral dissertation based on the European ENABLE-AGE Project, we aimed to demonstrate a systematic approach to synthesize research findings generated by large research projects as the basis for evidence-based interventions. The synthesized findings highlighted the complex interactions between objective and perceived aspects of housing and aspects of health in very old age, impacting on, for example, residential decision making. Independence in daily activity is influenced by the sociocultural care and service context. A familiar and safe neighborhood, a social network, and a good supply of services are important to perceptions of participation. Going further, we suggest housing-related interventions that address problems and challenges related to ongoing demographic changes. This article contributes to the development of strategies for knowledge translation, connecting research and practice and policy contexts struggling to meet the societal challenges that accompany population aging.